Peran perpustakaan madrasah dalam memajukan program literacy di lembaga pendidikan ke-Islaman - Mahfudz A. Junaidy (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2007)
Madrasa is one of the institution of the Islamic education which has big role in promoting literacy program., like Madrasa Nasriyah in Masjid ai-Aqsa. Madrasa Nasriyah also known as Madrasa AI-Ghazaliyah as a honor of Imam Gazali. He has finished his work there namely Book lhya al-'Ulum al-Din. We agree that every madrasa has library, and we call madrasa library. Key Words: Perpustakaan Madrasah, Lembaga Pendidikan, Literacy.